Muatan Lokal Schistosomiasis pada Anak Sekolah di Dataran Bada Kabupaten Poso Sulawesi Tengah - Ahmad Erlan; Hayani Anastasia; Gunawan Gunawan (Jurnal Vektor Penyakit, 2022)
ABSTRACT Schistosomiasis in Indonesia is caused by the trematode worm, Schistosoma japonicum, with the snail Oncomelania hupensis lindoensis as the intermediate host. This disease in addition to infecting humans also infects all types of mammals, both domesticated and wild animals. Chronic schistosomiasis reduces the patient's ability to work, and in some cases causes death in all age groups. Intestinal helminth infections in school-age children exacerbate malnutrition. Prolonged malnutrition and intestinal worm infection can lead to stunting in school-age children. The research used is a mixed-method, namely qualitative and quantitative data collection. Data were obtained by in-depth interviews with key informants and focus group discussions. Provide schistosomiasis subject matter to school children by measuring students' knowledge level through pre and post-test. The study was conducted in an endemic area of Bada schistosomiasis to January-November 2019. The number of samples of junior high school students who took the pre and post-test was 69 samples and 101 samples of elementary school students. Based on the statistical analysis found a significant increase in students' knowledge about schistosomiasis with a p-value <0.001. Community empowerment through the provision of schistosomiasis subject matter to school children is proven to be effective in increasing students' knowledge to reduce the risk of stunting in children, increase the scope of feces collection, and change community behavior for the better to avoid transmission and always work devoutly to clean the focus of snail. ABSTRAK Schistosomiasis di Indonesia disebabkan oleh cacing trematoda jenis Schistosoma japonicum dengan hospes perantara keong Oncomelania hupensis lindoensis. Penyakit ini selain menginfeksi manusia, juga menginfeksi semua jenis mamalia baik hewan peliharaan maupun binatang liar. Schistosomiasis kronis menurunkan kemampuan penderita dalam bekerja, dan beberapa kasus menimbulkan kematian pada semua golongan umur. Infeksi cacing usus pada anak-anak usia sekolah memperburuk malnutrisi. Malnutrisi berkepanjangan dan infeksi cacing usus dapat mengakibatkan stunting pada anak usia sekolah. Penelitian yang digunakan adalah mixed method yaitu pengumpulan data secara kualitatif dan kuantitatif. Data diperoleh dengan wawancara mendalam kepada informan kunci dan diskusi kelompok terarah. Memberikan materi pelajaran schistosomiasis kepada anak sekolah dengan mengukur tingkat pengetahuan siswa melalui pre dan post-test. Penelitian telah dilakukan di daerah endemis schistosomiasis Bada sejak Bulan Januari-November 2019. Jumlah sampel siswa sekolah tingkat pertama yang mengikuti pre dan post test 69 sampel dan siswa sekolah dasar 101 sampel. Berdasarkan analisis statistik ditemukan peningkatan yang signifikan pengetahuan pada siswa tentang schistosomiasis dengan nilai p-value<0,001. Pemberdayaan masyarakat melalui pemberian materi pelajaran schistosomiasis pada anak sekolah terbukti efektif meningkatkan pengetahuan siswa sehingga mengurangi resiko stunting pada anak-anak, meningkatkan cakupan pengumpulan tinja dan mengubah perilaku masyarakat menjadi lebih baik untuk menghindari penularan dan selalu bekerja bakti membersihkan fokus keong.